2000
DOI: 10.1242/dev.127.9.1845
|View full text |Cite
|
Sign up to set email alerts
|

Integration of FGF and TWIST in calvarial bone and suture development

Abstract: Mutations in the FGFR1-FGFR3 and TWIST genes are known to cause craniosynostosis, the former by constitutive activation and the latter by haploinsufficiency. Although clinically achieving the same end result, the premature fusion of the calvarial bones, it is not known whether these genes lie in the same or independent pathways during calvarial bone development and later in suture closure. We have previously shown that Fgfr2c is expressed at the osteogenic fronts of the developing calvarial bones and that, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…Initially identified in Drosophila where it is involved in mesodermal patterning and morphogenetic movement (23), Twist is a highly conserved protein and a master regulator of morphogenesis. Previous studies have also shown that Twist is important in bone development and is expressed in primary osteoblastic cells (24) and preosteoblasts (25). In situ analysis of murine embryonic development provided evidence that Twist abundance is reduced during endochondral and intramembranous fetal bone development (26).…”
Section: Discussionmentioning
confidence: 95%
“…Initially identified in Drosophila where it is involved in mesodermal patterning and morphogenetic movement (23), Twist is a highly conserved protein and a master regulator of morphogenesis. Previous studies have also shown that Twist is important in bone development and is expressed in primary osteoblastic cells (24) and preosteoblasts (25). In situ analysis of murine embryonic development provided evidence that Twist abundance is reduced during endochondral and intramembranous fetal bone development (26).…”
Section: Discussionmentioning
confidence: 95%
“…Intriguingly, consistent with the continuous transition mode as revealed by transcriptional and functional repertoires of mSMCs, a similar mode was observed in the regulatory network ( Figure 3B ). In addition, mSMC-associated modules (namely, M1, M4, and M5) included several reported ossification- or calcification-related TFs, including Dlx5 ( Shirakabe et al, 2001 ), Sox9 ( Augstein et al, 2018 ), Runx2 ( Byon et al, 2011 ), Rarg ( Pan et al, 2020 ), and Twist1 ( Rice et al, 2000 ; Bialek et al, 2004 ) Finally, we explored the distribution model of the top 20 cell-type-specific regulons for each cell type in eight modules and represented in a Sankey plot ( Figure 3C ). The results were showed for a specific cell type, and the top 20 regulons concentrated primarily in a module (e.g., top 20 regulons of SMCs in M3).…”
Section: Resultsmentioning
confidence: 99%
“…Between adjacent skull bones, OFs are present within the developing suture consisting of fibrous joints (Morriss-Kay and Wilkie, 2005;Rice et al, 2000;Wilkie and Morriss-Kay, 2001). Growth at the OFs occurs through intramembranous ossification, by which osteoprogenitors proliferate and differentiate directly into osteoblasts (Iseki et al, 1997(Iseki et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…During skull development, growth at the osteogenic fronts (OFs) occurs via intramembranous ossification, in which mesenchymal osteoprogenitors proliferate and differentiate directly into osteoblasts (Iseki et al, 1997(Iseki et al, , 1999Rice et al, 2000). A recent elegant study using single cell RNA-seq analysis demonstrated that one of the most significant OF-associated genes is Col22a1, which encodes cross-linking extracellular matrix (ECM) collagen (Holmes et al, 2020).…”
Section: Osteoblasts Near the Osteogenic Front Are Crucial For Intramembranous Ossificationmentioning
confidence: 99%
See 1 more Smart Citation